Chylothorax and Chylous-Like Diseases in Children: Clinical Management - Hermon, Michael; Tenner, Elias; Burda, Gudrun; Strohmaier, Wolfgang; Schlager, Gerald; Golej, Johann (Frontiers in Pediatrics, 2019)
Background: Chylothorax and chylous-like disease are rare conditions and difficult to treat. But, they may represent a potentially life-threatening disorder and important cause of morbidity and prolonged hospitalization, especially in critically ill children. Conservative as well as surgical therapeutic management strategies are continuously performed at our institution, however the results have never been evaluated and no guidelines for treatment recommendations have been put into practice so far. The objective of this retrospective study was to present a comprehensive and substantial evaluation of all relevant demographic data from children with the chylothorax and chylous-like disease and their clinical management. Methods: We retrospectively analysed data from all children with the diagnosis of chylothorax and chylous-like disease admitted to our pediatric intensive care unit between the years 1999 and 2012. Results: Data of 34 patients were analysed for this study. Gender distribution (M/F) was almost equal (19/15; 56%/44%). Thirty-one children (91%) developed chylothorax after surgery. Two children (6%) had idiopathic chylothorax and in one child (3%) congenital chylothorax was diagnosed. All study patients (n=34; 100%) received MBF/MCT therapy. In 14 children who received only this therapy we were quite successful, chest tube output droped from 100% to 4.7%. But, only 11(32%) children received somatostatin and 7(20%) children, respectively received beta-isodona. Different surgical interventions were performed in 6 patients (17%). All study patients received chest tubes to drain the pleural fluid and hence to relieve the chyle related symptoms. Conclusion: A combination of different conservative therapies was successful in most of our patients. Prevention, early diagnosis and treatment of potential complicactions may further improve success of conservative therapy especially in patients with postoperative chylothorax. In summary appropriate therapy of this condition may be lengthy but can prevent significant morbidity and mortality.